HUBUNGAN PENERAPAN STRATEGI DALAM METODE EVERY ONE IS A TEACHER HERE DENGAN PENINGKATAN MOTIVASI BELAJAR PAI - NURLISMA (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2020)
Student participation is very important in the learning process, in addition to the activeness and learning outcomes achieved. Teachers must always be able to pay attention to every method and learning strategy that is suitable for students' conditions, the method every one is a teacher here is a method that is easy to use to obtain large and responsible student participation in class. Therefore, the use of this method is very hopeful of educators so that students can get maximum learning outcomes. As a concept for active learning, namely a process of teaching and learning activities in which students are involved intellectually and emotionally so that they can really play a role and participate actively in carrying out learning activities. The application of the every one is a teacher here method in learning Islamic religious education is the right choice of a teacher, students will easily master the material that will be delivered by a teacher and they will more quickly understand and understand teachings in the form of concepts and principles in material topics being taught, this is based on the main student-centered activities with teacher guidance, and the teacher is not the main role, the use of this method will be able to increase student motivation.